Characteristics of Motor Development in Children with Autism Spectrum Disorder: A Systematic Review - Spies, Márcia Franciele (2023)
The present study aimed to synthesize and analyze the scientific production about the motor development (MD) characteristics in children with autistic spectrum disorder (ASD) through systematic literature revision. In this sense, Eric/Thesaurus, Web of Science, SciELO, Scopus, ASP/EBscos and Redalyc databases were selected. For the articles' identification in the databases, the descriptors "child development", "autism spectrum disorder", "motor skills disorder" and "motor development" were listed, and their terms in portuguese as well. These descriptors were identified between the descriptors in health sciences (DiHS), BVS and Thesaurus (Eric) for embracing areas of health and education. The final sample was composed by five different studies that presented data from different motor assessment batteries. The results characterized the MD in children with ASD as atypical, presenting meaningful deficits in all the motor areas, being fine coordination, balance and body scheme the most talked about.